Application of accrual and cash accounting: Implications for small and medium enterprises in Metro Manila - Cudia, Cynthia P. (Animo Repository, 2008)
This study aims to determine which between the two methods of accounting, accrual or cash method, is more applicable to SMEs in Metro Manila. Accordingly, this study aims to determine the factors that influence SMEs in Metro Manila to apply the chosen accounting method. Some implications of using accrual and cash accounting are specified. This includes implications on qualitative characteristics of financial information, on income statements and balance sheet, on SMEs' liquidity and profitability positions, and implications of using cash/modified-cash basis converted to accrual basis at year-end. The results of the study provide insights on the applicability of the Exposure Draft, as to the bases of accounting. This study is also timely as the final standards are expected to be issued by the IASB in the second half of 2008.